Validity and reliability of a medicine ball explosive power test - Stockbrugger, A.; Haennel, R. G. (The Journal of Strength and Conditioning Research, 2001)
The purpose of this study was to evaluate the validity and reliability of a medicine ball throw test to assess explosive power. Twenty competitive sand volleyball players (10 male players, 10 female players) performed a medicine ball throw and a standard countermovement vertical jump. The subjects attended 2 sessions; at each session, 3 attempts of each test were completed. The movement pattern for the medicine ball throw was a backward overhead toss. To standardize for body weight, a power index was calculated for the countermovement vertical jump using the Lewis formula. Validity was assessed using the best score for both the throw and the jump, and reliability was assessed using the best score from each session. There was a strong correlation between the distance of the medicine ball throw and the power index for the countermovement vertical jump (r = 0.906, p < 0.01). For the countermovement vertical jump, the test-retest reliability was 0.993 (p < 0.01), and for the medicine ball throw, the test-retest reliability was 0.996 (p < 0.01). These findings suggest that the medicine ball throw test is a valid and reliable test for assessing explosive power for an analogous total-body movement pattern and general athletic ability.